2015
DOI: 10.1038/jcbfm.2015.57
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the ALS-Causing Variant hSOD1G93A Leads to an Impaired Integrity and Altered Regulation of Claudin-5 Expression in an in Vitro Blood–Spinal Cord Barrier Model

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder characterized by progressive paralysis due to the loss of primary and secondary motor neurons. Mutations in the Cu/Zn-superoxide dismutase (SOD1) gene are associated with familial ALS and to date numerous hypotheses for ALS pathology exist including impairment of the blood-spinal cord barrier. In transgenic mice carrying mutated SOD1 genes, a disrupted blood-spinal cord barrier as well as decreased levels of tight junction (TJ) proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Although the disruption of the BSCB in ALS has been previously reported ( Garbuzova-Davis et al, 2007a , 2007b ; Zhong et al, 2008 ), the nature of the primum movens has remained debated: Is BSCB impairment driven by MN dysfunction or is it a MN-independent event? Some (controversial) evidence has pointed toward an MN-independent origin: Endothelial cells expressing mutant SOD1 in vitro display a cell-autonomous disruption of TJs because of the misfolded protein itself ( Meister et al, 2015 ). At the same time, endothelial cell–selective excision of the mutant SOD1 transgene does not prevent the breakdown of the BSCB nor affect the survival of the transgenic mice ( Zhong et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the disruption of the BSCB in ALS has been previously reported ( Garbuzova-Davis et al, 2007a , 2007b ; Zhong et al, 2008 ), the nature of the primum movens has remained debated: Is BSCB impairment driven by MN dysfunction or is it a MN-independent event? Some (controversial) evidence has pointed toward an MN-independent origin: Endothelial cells expressing mutant SOD1 in vitro display a cell-autonomous disruption of TJs because of the misfolded protein itself ( Meister et al, 2015 ). At the same time, endothelial cell–selective excision of the mutant SOD1 transgene does not prevent the breakdown of the BSCB nor affect the survival of the transgenic mice ( Zhong et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the driver(s) of BSCB disruption in ALS and its ultimate impact on disease progression are still debated. It has been hypothesized that damage of the BSCB may arise as a cell autonomous consequence of mutant SOD1 accumulation in endothelial cells: endothelial cells isolated from SOD1 G93A mice and immortalized mouse endothelial cells expressing the human G93A mutant SOD1 display reduced levels of claudin-5 (CLN-5) and decreased transendothelial resistance (Meister et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In peripheral nerves, claudin‐5 is present in endothelial cells of endoneurial vessels, as well as mesaxons and Schmidt–Lantermann incisures . In the spinal cord, claudin‐5 is reduced (e.g., in amyotrophic lateral sclerosis via the β‐catenin/AKT/FOXO1 pathway, and in hSOD G93A in transgenic endothelial cells). In CCI and SNI neuropathy, we observed that claudin‐5 mRNA in whole lumbar spinal cord and claudin‐5 immunoreactivity in spinal cord capillaries are reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, for bEnd.3 cells, the permeability to [C 14 ]-inulin (Perkin-Elmer, Waltham, MA, USA) was analyzed as described previously. 19…”
Section: Methodsmentioning
confidence: 99%